Cardiopulmonary function during exercise in heart failure with reduced ejection fraction following baroreflex activation therapy. (October 2022) - Nottebohm, Pia I.; Dumitrescu, Daniel; Hamacher, Stefanie; Hohmann, Christopher; Madershahian, Navid; Baldus, Stephan; Reuter, Hannes; Halbach, Marcel
Purpose: Baroreflex activation therapy has favorable effects in heart failure patients. We report the results of a single-center study of baroreflex activation therapy in heart failure with reduced ejection fraction including cardiopulmonary exercise testing for the first time to show the effect on exercise capacity. Methods: A total of 17 patients were treated with baroreflex activation therapy. Eligibility criteria were the New York Heart Association class ⩾III and ejection fraction ⩽35% on guideline-directed medical and device therapy. The New York Heart Association class, quality of life, and 6-min hall walk distance were assessed in all patients. Twelve patients underwent cardiopulmonary exercise testing before and 8.9 ± 6.4 months after initiation of baroreflex activation therapy. Results: The New York Heart Association class and 6-min hall walk distance improved after baroreflex activation therapy, while quality of life remained stable. Weight-adapted peak oxygen uptake increased significantly from 10.1 (8.2–12.9) ml/min/kg to 12.1 (10.4–14.6) ml/min/kg ( p = 0.041). Maximal heart rate was stable. Maximal oxygen pulse increased from 9.7 (5.5–11.3) to 9.9 (7.1–12.1) ml/heartbeat ( p = 0.047) in 10 patients with low maximal oxygen pulse at baseline (<16.5 ml/heartbeat). There was no significant change in maximal oxygen pulse in the whole cohort. Ventilatory efficiency remained stable. Conclusion: Weight-adapted peak oxygen uptake improved after baroreflex activation therapy, pointing to an enhanced exercise capacity. Ventilatory efficiency and heart rate did not change, while oxygen pulse increased in patients with low oxygen pulse at baseline, indicating an improvement in circulatory efficiency, that is, a beneficial effect on stroke volume and peripheral oxygen extraction.